Effects of Panax ginseng extract on exercise-induced oxidative stress - Kim, S. H.; Park, K. S.; Chang, M. J.; Sung, J. H. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: This study was designed to study the effects of Panax ginseng extract (PGE) on lipid peroxidation and scavenger enzymes induced by an acute exhaustive exercise in sedentary humans. Methods: Seven healthy male subjects performed 2 exhaustive incremental exercises on the treadmill before and after 8 weeks' PGE ingestion (2 g each time, 3 times a day) as the control and PGE exercise, respectively. V.O2, HR, and exercise duration during exercise were measured. Blood samples were collected at rest, and immediately, 10 and 30 min after each test and used to measure malondialdehyde (MDA), catalase (CAT), and superoxide dismutase (SOD). Results: PGE administration significantly increased exercise duration until exhaustion by 1.5 min (p<0.05). MDA was significantly elevated following both trials (p<0.01), however, it was attenuated after PGE administration (p<0.01). CAT and SOD activities following exercise were significantly elevated, but the activities following control exercise were much lower than those following PGE exercise. Conclusion: These results suggest that the elevation in CAT and SOD activities as scavenger enzymes after PGE administration result in decease of MDA level as one of PGE action mechanisms and consequently, prolong exercise duration until exhaustion. These findings support scientific claims that ginseng has ergogenic properties in facilitating recovery from exhaustive exercise.